Peran Badan Penanggulangan Bencana Daerah (BPBD) Kota Yogyakarta dalam Penanggulangan Bencana Banjir di Kelurahan Pandeyan Kemantren Umbulharjo Kota Yogyakarta - Pujianti, Pujianti; Gerry Katon, Mahendra (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
Almost every year, Indonesia experiences flood disasters, such as those experienced in Pandeyan Village. Thus, Pandeyan Subdistrict needs the role of Yogyakarta City BPBD in flood disaster management efforts. This research aims to determine and analyze the role of the Yogyakarta City BPBD in managing flood disasters in Pandeyan Village, Kemantren Umbulharjo, Yogyakarta City. This research uses descriptive qualitative research and uses data collection techniques such as observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that the role of Yogyakarta City BPBD in flood disaster management has carried out and fulfilled its role in accordance with the role theory put forward by Sondang P. Siagian. Yogyakarta City BPBD has played a role in flood disaster management efforts through several programs and activities carried out in Pandeyan Village